Endurance training does not alter the level of neuronal nitric oxide synthase in human skeletal muscle - Frandsen, U.; Höffner, L.; Betak, A.; Saltin, B.; Bangsbo, J.; Hellsten, Y. (Journal of Applied Physiology, 2001)
The effect of endurance training on neuronal nitric oxide synthase (nNOS) content and distribution in muscle was investigated. Seven male subjects performed 6 wk of one-legged knee-extensor endurance training (protocol A). Muscle biopsies, obtained from vastus lateralis muscle in the untrained and the trained leg, were analyzed for nNOS protein and activity as well as immunohistochemical distribution of nNOS and endothelial nitric oxide synthase (eNOS). Muscle biopsies were also obtained from another seven male subjects before and after 6 wk of training by endurance running (protocol B) and analyzed for nNOS protein. No difference was found in the amount of nNOS protein in the untrained and the trained muscle either with protocol A or protocol B (P > 0.05). In protocol A, the activity of nNOS was 4.76 ± 0.56 pmol · mg protein1 · min1 in the control leg, and the level was not different in the trained leg (P > 0.05). nNOS was present in the sarcolemma and cytosol of type I and type II muscle fibers, and the qualitative distribution was similar in untrained and trained muscle. The number of eNOS immunoreactive structures and the number of capillaries per muscle fiber were higher (P < 0.05) after training than before. The present findings demonstrate that, in contrast to findings on animals, nNOS levels remain unaltered with endurance training in humans. Evidence is also provided that endurance training may increase the amount of eNOS, in parallel with an increase in capillaries in human muscle.